SAT0561 Persistence of Biologic Therapy in Psoriatic Disease: Results from the Psoriasis Longitudinal Assessment and Registry (PSOLAR). (9th June 2015) - Menter, A.; Papp, K.; Krueger, G.G.; Augustin, M.; Kerdel, F.; Gooderham, M.; Goyal, K.; Fakharzadeh, S.; Langholff, W.; Sermon, J.; Calabro, S.; Pariser, D.
Abstract : Objectives: We evaluated persistency of biologic use in pts with psoriasis (PsO) and psoriatic arthritis (PsA) in PSOLAR. Methods: PSOLAR evaluates outcomes for PsO pts eligible to receive treatment with systemic agents. Among PSOLAR pts, 36% (n=4317) have self-reported PsA. Duration of therapy was defined as time (days) between first dose of biologic and first of: 1) discontinuation 2) switch 3) registry withdrawal or 4) last data cut (Aug 23, 2013). Separate analyses were performed for: 1st line (bio-naïve), 2nd line, and 3rd line usage to reduce confounding associated with prior exposures for the overall and PsA populations. Persistence was assessed by Kaplan-Meier analysis for time to therapy stop/switch separately for ustekinumab (UST), infliximab (IFX), adalimumab (ADA), and etanercept (ETN). Cox proportional hazard regression analysis compared time to stop/switch of UST with other biologics for each cohort. Results: Most starts were attributed to UST (1833 pts) and ADA (1303) with fewer starts for ETN (537) and IFX (327). Among UST starts, the proportions of 1st, 2nd and 3rd line usage were 20%, 31%, and 30%; ADA starts 31%, 48%, and 15%; ETN starts 54%, 29% and 13%; IFX starts 19%, 28% and 32%, respectively. Baseline clinical characteristics were generally comparable across biologics and cohorts. Fewer pts discontinued UST than IFX, ETN, and ADA in all 3 lines. Median duration of therapy was generally longer for UST vs anti-TNF therapies. For 1st line starts, better persistence was observed for UST based on significant differences in time to stop/switch for each biologic vs UST (IFX vs UST: HR3.04; CI:1.66-5.57; p=0.0003; ADA vs UST: HR4.99; CI:3.39-7.35; p<0.0001; ETN vs UST: HR5.59; CI:3.77-8.29; p<0.0001). Similar results were observed for 2nd and 3rd line starts. In the subgroup with self-reported PsA, for 1st line starts, better persistence was observed with UST vs ETN (HR 2.53; CI 1.39-4.62; p=0.0024); no significant differences were seen for UST vs IFX and ADA. UST had better persistence vs anti-TNFs in the analyses of 2nd and 3rd line starts. Reasons for stop/switch were similar across biologics and cohorts.Data were not adjusted for differences among cohorts, e.g. MTX use, insurance, administration setting, and region. Conclusions: Persistence of UST therapy in psoriatic disease was significantly better than anti-TNF therapies in biologic-naïve and experienced pts, with lower rates of stopping/switching and higher median days on therapy. Disclosure of Interest: A. Menter Grant/research support from: Janssen Scientific Affairs, LLC, K. Papp Grant/research support from: Janssen Scientific Affairs, LLC, G. Krueger Grant/research support from: Janssen Scientific Affairs, LLC, M. Augustin Grant/research support from: Janssen Scientific Affairs, LLC, F. Kerdel Grant/research support from: Janssen Scientific Affairs, LLC, M. Gooderham Grant/research support from: Janssen Scientific Affairs, LLC, K. Goyal Employee of: Janssen Scientific Affairs, LLC, S. Fakharzadeh Employee of: Janssen Scientific Affairs, LLC, W. Langholff Employee of: Janssen Scientific Affairs, LLC, J. Sermon Employee of: Janssen-Cilag, S. Calabro Employee of: Janssen Scientific Affairs, LLC, D. Pariser Grant/research support from: Janssen Scientific Affairs, LLC